Pengaruh Modal Usaha dan Jam Kerja Terhadap Pendapatan Pedagang Kelontong di Desa Nagori Bosar Kabupaten Simalungun - Siahaan, Anton Luvi; HS, Sahat Renol (Universitas Pendidikan Ganesha, 2024)
This research was conducted with the aim of finding out the effect of business capital and working hours on the income of grocery traders in Nagori Bosar Village, Simalungun Regency. This research uses descriptive quantitative research. The population in this study was all grocery traders in Nagori Bosar Village, totaling 45 people, so a saturated sample was used. The data collection techniques used are observation, documentation, and questionnaires, where the questionnaire will be tested for validity and reliability before conducting research. The data analysis techniques used by researchers are classic assumption tests such as normality tests, multicollinearity tests, and heteroscedasticity tests, as well as hypothesis tests such as multiple linear regression, t-tests, F-tests, and coefficients of determination. The results of this research are that business capital and working hours have a positive and significant effect on grocery traders' income, both partially and simultaneously (t-test and F-test). Furthermore, business capital and working hours contribute 50.2% to traders' income, while another 49.8% is explained by other variables not examined in this research.